1993
DOI: 10.1093/jac/31.suppl_e.1
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro concentration of azithromycin in human phagocytic cells

Abstract: The in-vitro intraphagocytic uptake and retention of azithromycin in both human polymorphonuclear leucocytes (PMN) and alveolar macrophages was measured by an improved high-performance liquid chromatography (HPLC) method that was approximately three-fold more sensitive than previous methods. Azithromycin was accumulated in PMN and alveolar macrophages (about 300-fold), with maximum uptake being obtained after incubation for 60 min. Azithromycin was eliminated only partially from the cells during the washing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…The MIC is above the reported peak serum level of 0.4 g/ml following a 500-mg oral dose of azithromycin (6) and 3.1 g/ml following a 1-g dose by intravenous infusion (9) and is above the NCCLS breakpoint for susceptibility (15). Azithromycin, however, achieves high intracellular concentrations (16) and activity (18). The discordance between in vitro susceptibility and in vivo effectiveness is probably explained by the predominantly intracellular location of serovar Typhi (27).…”
Section: Discussionmentioning
confidence: 99%
“…The MIC is above the reported peak serum level of 0.4 g/ml following a 500-mg oral dose of azithromycin (6) and 3.1 g/ml following a 1-g dose by intravenous infusion (9) and is above the NCCLS breakpoint for susceptibility (15). Azithromycin, however, achieves high intracellular concentrations (16) and activity (18). The discordance between in vitro susceptibility and in vivo effectiveness is probably explained by the predominantly intracellular location of serovar Typhi (27).…”
Section: Discussionmentioning
confidence: 99%
“…When laparoscopic surgery has been compared with minilaparotomy, earlier studies reported that laparoscopic surgery was superior in reducing hospital stay and postoperative dysfunction as well as leading to a quicker return to normal activities. However, subsequent reports did not show any improvement in postoperative recovery and respiratory impairment or any reduction in neuroendocrine response and cortisol production (4,24,34). When laparoscopic surgery involving a larger extent of surgical dissection, such as laparoscopic adrenalectomy, was compared with open surgery, white blood cell count and CRP level, two parameters that reflect acute inflammation, did not differ significantly between groups (6).…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels after oral administration are 0.04 to 0.4 g/ml (557). Azithromycin shows excellent penetration into most tissues and achieves intracellular concentrations inside macrophages and neutrophils that are 10 to 100 times greater than serum concentrations, with slow release from this intracellular site (558,559). The drug has a long half-life of 2 to 3 days, allowing once-daily administration, and is safe to use in children.…”
Section: Azithromycinmentioning
confidence: 99%